Tawa dan Identitas Lokal: Figur Kedok Menyon sebagai Representasi Sosial dalam Kesenian Singa Dangdut - Isad Suhaeb (Haluan Sastra Budaya, 2025)
The Singa Dangdut performance in Indramayu offers more than just music and dance entertainment. It also features a comedic character named Menyon, who becomes the center of attention in creating a festive atmosphere. This article examines the Menyon mask figure as a form of social representation and a symbol of local identity in Indramayu. Using an ethnographic approach and cultural representation theory, this study analyzes how the laughter evoked by Menyon is not merely entertaining but also carries social critique, class expression, and the reinforcement of communal solidarity. Data were collected through direct observation of Singa Dangdut performances, interviews with performers, and visual analysis of the mask design. The findings reveal that The Menyon mask plays a strategic role as a medium of dynamic local cultural expression. reflecting tensions between tradition and modernity, while also serving as a safe space for symbolic public expression. Thus, the Menyon character is not merely a stage clown but also a cultural agent who embodies social values, collective identity, and the everyday dynamics of the people of Indramayu.